Gestão escolar e inclusão digital: uso da tecnologia digital como recurso didático na escola Estelita Timóteo - PE - Rêgo, Ana Flávia Franco do (2016)
In the context of twenty-first century, human capacity, innate and voluntary learning has increasingly given way to a kind of potential condition, almost involuntary of, "learning how to learn" .In this sense, the qualification to work or continuing education has been established as the new order of employment, efficiency and competence to conquer space and to confront the dynamics and problems that challenge the subject to appropriate positions in the context of learning organizations. This way, the search for learning in contemporary society becomes effective means for the learner as active and interactive subject in the society of which it is part. From this perspective, this study aimed to analyze the management of continuing education in the context of teaching activities in public state of Pernambuco education, and the local of data collection was the city of Carpina. In methodological terms, this is a field research, nuanced by qualitative and quantitative approach, typified as exploratory, bibliographical and documentary. Data collection used semi-structured interviews and mixed questionnaire, applied to social actors from the three schools selected, respectively: three managers, three supporting educators and 45 teachers, 15 of each school unit, whose interpretive processing of data collected was founded in the content analysis. The results showed how the continuing education directly affects the quality of education and, consequently, in the multiple forms of learning. Teachers tend to prefer continuing education programs as promoted by the management team of the school where they work because they believe that these moments are much more useful and reflections and studies gain a harnessing and a better use than in training promoted outside the school environment even though variance with the concept of continuing education as formal education. The participation of teachers as one of the sectors involved in the preparation of the Pedagogic Political Project, strengthens these moments of training and ensures their implementation in a satisfactory manner, although the idea of ”training” is a difficult disproportion to be lacking . Therefore, the teaching continuing education policy of Pernambuco, associated with the didactic-pedagogical and curricular, should also return to the education for life, making the critical pedagogical practice itself, and not reproducing the intentional and ideological purposes of power. Keywords: learners organizations . teacher training . Management of continuing